2022
DOI: 10.3233/ch-221546
|View full text |Cite
|
Sign up to set email alerts
|

Association of coagulation factors profile with clinical outcome in patient with COVID-19 and acute stroke: A second wave cohort study

Abstract: INTRODUCTION: The second wave of COVID-19 in Indonesia occurred due to delta variant transmission with up to 2266 cases. This variant could cause higher rate of morbidities and mortalities. This study reported coagulation profile of COVID-19 patients with acute stroke and its association with patients’ outcome. METHOD: This is a cohort-retrospective study conducted during the second wave of COVID-19, June-August 2021 in Cipto Mangunkusumo General Hospital. Inclusion criteria were adult patients with confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Among those, neutrophil to lymphocyte ratio (NLR) emerged as a cost-effective predictor of complications and high values suggest poor prognosis in patients with severe Covid-19 [2,6]. The hypercoagulable state is characterised by an increased D-dimer, fibrinogen and prothrombin time, which <ins cite="mailto:User" datetime="2022-12-18T21 : 00">along with blood hyperviscosity</ins> leads to <ins cite="mailto:User" datetime="2022-12-18T21 : 01">venous and arterial</ins> thrombotic complications [7][8][9][10][11][12][13][14]. Among Covid-19 patients a higher incidence of venous thromboembolisms (VTE) has been observed across studies, however the reported prevalence rate varies greatly, ranging from 8 to 76% for pulmonary embolism (PE) and from 7 to 85% for deep vein thrombosis (DVT), with a higher prevalence among ICU patients [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Among those, neutrophil to lymphocyte ratio (NLR) emerged as a cost-effective predictor of complications and high values suggest poor prognosis in patients with severe Covid-19 [2,6]. The hypercoagulable state is characterised by an increased D-dimer, fibrinogen and prothrombin time, which <ins cite="mailto:User" datetime="2022-12-18T21 : 00">along with blood hyperviscosity</ins> leads to <ins cite="mailto:User" datetime="2022-12-18T21 : 01">venous and arterial</ins> thrombotic complications [7][8][9][10][11][12][13][14]. Among Covid-19 patients a higher incidence of venous thromboembolisms (VTE) has been observed across studies, however the reported prevalence rate varies greatly, ranging from 8 to 76% for pulmonary embolism (PE) and from 7 to 85% for deep vein thrombosis (DVT), with a higher prevalence among ICU patients [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The coagulation profile of COVID-19 patients who had an acute stroke and its relationship to patients' outcomes were reported in a study. The baseline D-dimer value and its peak value during hospitalisation were significantly greater in patients who had a poor outcome, demonstrating that the D-dimer can be a predictor of death in COVID-19 patients with acute stroke [25].…”
Section: Effect Of Sars-cov-2 On Haemostasismentioning
confidence: 89%
“…[10] Oleh sebab itu rekomendasi pemberian antikoagulan dapat diberikan pada pasien stroke iskemik akut dengan infeksi COVID-19 dengan kadar Ddimer yang tinggi. [10,16] Tatalaksana stroke iskemik dengan infeksi COVID-19 pada penelitian ini pada prinsipnya sama dengan stroke iskemik tanpa COVID-19 yaitu dengan pemberian antiplatelet pada sebagian besar pasien (83,3%). Adapun terapi trombolisis tidak tercantum pada data penelitian, karena di rumah sakit ini belum tersedia.…”
Section: Pembahasanunclassified